PENGARUH KEPERCAYAAN DAN RISIKO TERHADAP KEPUTUSAN PEMBELIAN MELALUI SIKAP PENGGUNA PADA SITUS BELANJA ONLINE LAZADA.COM (Studi pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro Semarang) - Riko Ashari; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2018)
The sales volume of cigarettes in Indonesia continues growing, as the average daily Marketing system right now is about involve the technological innovation changes. In Indonesia, the marketing system technological changes calls e-commerce like the form of online purchasing site to see the development of internet users in Indonesia from year to year experienced significant growth. One of the online purchasing sites in Indonesia is Lazada.com which is a place for businesses to market their products and provide various facilities and product diversity for consumers to meet the needs ranging from primary to tertiary.This study use explanatory research type, with population of 100 respondents who have access and make purchasing decisions online at Lazada.com site. The technique of sampling in this research use non-probability with purposive technique indeed. Questionnaires were chosen to collect data from respondents. Data analysis methods used are Partial Least Square (PLS) analysis, Mediation / Intervening Testing using Variance Accounted For (VAF) and Fit Model Indicator (Model of Indices) using WarpPLS 5.0 application.The results of the analysis show that the direct effect test on this model has a positive and significant effect on trust variables to purchase decision, user attitude variable to purchase decision, and trust variable to user attitude. The direct impact test of risk variable has a negative and significant effect to the purchasing decision. The indirect test for trust variables has a positive and significant influence, and the risk variables show the negative and significant influence of each to decision through user attitude. The influence of user attitude variable as mediator on trust variable and risk variable to purchasing decision that is partial mediation.Suggestions in this research is to improve distribution system both in supply chain and expedition partner, also need to improve standard for seller credibility.